Creating Policy Space : Responsive Design and Streamlined Conditionality in Recent Low-Income Country Programs. (Policy Papers; Policy Paper, 2009)
An analysis of recent programs in low-income countries, covering countries with continuous program engagement with the IMF throughout the period 2007-09, shows that program design has been adapted to provide expanded policy space in response to the food and fuel price shocks of 2007-08 and to the global financial crisis that followed. The analysis also finds that structural conditionality in Fund-supported programs in low-income countries has become more streamlined, with a dominant focus on public sector resource management and accountability.